Skin in the game: the use of sensing smart fabrics in tennis costume as a means of analyzing performance - Chittenden, T. (Fashion and Textiles, 2017)
Underlying the surface decoration and cut of contemporary tennis costume is a fabric that enacts its own performance and studies the athlete who wears it. Whilst designers such as Teddy Tinling created tennis costumes that brought glamour and theatrical flair to the player`s performance, modern sports companies are increasingly using costume to approach human performance from a big data perspective. In the late nineteenth century, women playing tennis wore corsets and long skirts which impeded movement; today, the top players utilize fabric science that enables costume to control and record the temperature, sweat and muscle movement of the performer, whilst also presenting a vehicle to showcase their personality through their aesthetic choices. Smart fabrics allow for greater and more precise control over how our bodies perform, and they similarly alter our understanding of materiality and bodily presence with regards to fashion. The use of smart fabrics in sports, where the patterns of data collected by the costume visually and numerically display the conditions of the player/performance, holds potential for the ways in which we interrogate the interrelationship of clothing and performance across a range of arenas. For fashion research this means it is now possible not just to look at a costume but to look through it, via biometric capture, to a performance realized in data space. It is this duality of costume both in and as performance space that provokes this article to raise questions about the changeable nature of smart clothing and its relationship to the sporting body.